Preprints and preprint servers as academic communication tools - Galbán Rodríguez, Ernesto (Revista Cubana de Información en Ciencias de la Salud, 2019)
Preprints and preprint servers comprise the articulation of the ultimate and most proximal node to publishing the scientific results in academic journals. Therefore, in this review, the concept, development, advantages and limitations of preprints and preprint servers are analyzed, attending to their main function as publicly available repositories of manuscripts on the way to getting published. Moreover, an analysis of the motor forces contributing to their establishment to communicate research results among scientific communities is given, with their classification (journal, non-journal and mixed servers; subject repositories), as well as debate on the most successful (arXiv) and debated (Biology, Chemistry) servers, preprint formats, and their relationship with information phenomena such as open access, open archiving, digital information certification, information retrieval, and the added value through immediacy in availability and citation in comparison with published articles. Examples of their integration with ongoing communicational processes are discussed, such as migration of editors from journals to preprint servers to channel up manuscripts, open peer review strategies and scientific community engagement. A list of the most relevant preprint servers until 2018, their characteristics, general stats of their preprints and citation counts in Scopus is included.